Государственный контроль и обеспечение качества лекарств на фармацевтическом рынке РА - М. Г. Бегларян (Հայաստանի ԳԱԱ)
Դեղագործական շուկան ունի իր որոշակի առանձնահատկությունները, որոնք պայմանավորված են, մի կողմից, դեղերի` որպես յուրահատուկ ապրանքի շրջանառությամբ, քանի որ այն ունի սոցիալական նշանակություն և կապված է մարդկանց առողջության հետ, իսկ մյուս կողմից էլ նրան բնորոշ են այլ տնտեսական համակարգերի գործառույթները նույնպես: Դեղագործական շուկան բարդ տնտեսական մեխանիզմ է, որը գտնվում է ներքին և արտաքին գործոնների ազդեցության տակ: Այդ գործոններն ազդում են ինչպես դեղագործական շուկայի տնտեսավարող սուբյեկտների, այնպես էլ բնակչության պահանջարկի վրա: Among the specificities of the pharmaceutical market in current days there is on one hand the uniqueness of drugs as products, since they possess both health and social significance and, on the other hand, their being of normal products, manifesting all the other economic characteristics. Pharmaceutical market is a complex system which is influenced by a set of internal and external factors. These factors affect both economic entities of the pharmaceutical market and the demand for drugs in the population
Keywords: Pharmacy and materia medica; Medicine